Influence of fluorine substitution on the molecular conformation of 3 `-deoxy-3 `-fluoro-5-methyluriaine - Aher, Manisha N.; Erande, Namrata D.; Kumar, Vaijayanti A.; Fernandes, Moneesha; Gonnade, Rajesh G. (Acta Crystallographica Section C-Structural Chemistry, 2020)
{Fluorine substitutions on the furanose ring of nucleosides are known to strongly influence the conformational properties of oligonucleotides. In order to assess the effect of fluorine on the conformation of 3'-deoxy-3'-fluoro-5-methyluridine (T-R(F)), C-10 H13FN2O5, we studied its stereochemistry in the crystalline state using X-ray crystallography. The compound crystallizes in the chiral orthorhombic space group P2(1)2(1)2(1) and contains two symmetry-independent molecules (A and B) in the asymmetric unit. The furanose ring in molecules A and B adopts conformations between envelope (E-2, 2'-endo
Keywords: crystal structure; fluoro nucleoside; pseudorotation parameter; sugar puckering; uridine